2018
DOI: 10.1080/20018525.2018.1478593
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of persistent asthma in young adults

Abstract: Objective: The aim of the study was to evaluate determinants for the prognosis of asthma in a population-based cohort of young adults.Design: The study was a nine-year clinical follow up of 239 asthmatic subjects from an enriched population-based sample of 1,191 young adults, aged 20–44 years, who participated in an interviewer-administered questionnaire and clinical examination at baseline in 2003–2006. From the interview, an asthma score was generated as the simple sum of affirmative answers to five main ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(51 reference statements)
1
4
1
Order By: Relevance
“…Other cross-sectional research has also shown that smoking was associated with poor asthma control,10 11 13 and unadjusted prospective studies have also indicated that smoking predicted poor asthma control and asthma exacerbation over time,46 47 but these studies also did not remove people with COPD or adjust for cumulative past smoking and other smoke exposures. In contrast, at least one study that carefully controlled for these factors did not show an association between smoking and new asthma48; rather, similar to our study, use of controller medications at baseline was associated with persistence of asthma 48…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Other cross-sectional research has also shown that smoking was associated with poor asthma control,10 11 13 and unadjusted prospective studies have also indicated that smoking predicted poor asthma control and asthma exacerbation over time,46 47 but these studies also did not remove people with COPD or adjust for cumulative past smoking and other smoke exposures. In contrast, at least one study that carefully controlled for these factors did not show an association between smoking and new asthma48; rather, similar to our study, use of controller medications at baseline was associated with persistence of asthma 48…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, at least one study that carefully controlled for these factors did not show an association between smoking and new asthma 48 ; rather, similar to our study, use of controller medications at baseline was associated with persistence of asthma. 48 …”
Section: Discussioncontrasting
confidence: 49%
“…Of these, five studies exclusively included new adultonset asthma. 29,[38][39][40][41] Although the remaining nine studies included both adult-and childhoodonset asthma, [42][43][44][45][46][47][48][49][50] the participants were adults at the time of enrolment. Tupper et al included 62% adult-onset asthma and 38% childhood-onset asthma, and this report includes only data from the former group.…”
Section: Remission In the Adult Asthma Populationmentioning
confidence: 99%
“…3,7,9 Intermediate-diagnosed asthma (12-39 years) was in remission in 17.9% of subjects, which settles between earlier findings. 11,30 The diagnosis-age definition in this group reflects quite well those of adult-onset or late-onset asthma in previous studies comparing asthma by age of onset because older subjects have been left out in most of them. 25,30 Interestingly, exercise 2 to 3 times per week was the only significant risk factor of nonremission in this group, which however lost its significance if subjects reporting current asthma medication use but not symptoms were considered as remitted.…”
Section: Discussionmentioning
confidence: 78%
“…Other studies have similarly found only few risk factors of nonremission in subjects with similar diagnosis age: nasal polyps, allergic sensitization, worse lung function at baseline, inhaled corticosteroid use. 10,11,17,30 Daily physical activity has also been found to decelerate the loss of lung function in the long term in adult-onset asthma. 31 Only 5% of subjects with late-diagnosed asthma were currently in remission.…”
Section: Discussionmentioning
confidence: 99%